2005
DOI: 10.1111/j.1472-765x.2005.01667.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and recovery rates achieved using direct plate and enrichment/immunomagnetic separation methods for Escherichia coli O157:H7 in minced beef and on bovine hide

Abstract: Aims: To assess the detection and recovery rates achieved with commonly used cultural methods for the enumeration and recovery of Escherichia coli O157:H7 from minced beef and bovine hide. Methods and Results: Minced beef and bovine hide were inoculated with varying concentrations (log 10 1AE58-2AE58 CFU g)1 and log 10 2AE42-4AE49 CFU 100 cm 2 respectively) of E. coli O157:H7 and recovered using a direct plate method or an enrichment/immunomagnetic separation (IMS) method and then plated onto SMAC or SMAC-CT i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…We therefore used the information reported by O'Brien et al (2005) to generate a cumulative frequency distribution. Because the number of cells recovered are not the total bacteria in the carcass (I th ), the model introduced a recovery factor (R f ) to consider this aspect with an uniform distribution ranging from 0.5 to 1.5 log 10 , using the information reported by O'Brien et al (2004). Bacon et al (2000) reported a reduction in the level of the microorganisms on the carcass compared to the hide level.…”
Section: Processingmentioning
confidence: 99%
“…We therefore used the information reported by O'Brien et al (2005) to generate a cumulative frequency distribution. Because the number of cells recovered are not the total bacteria in the carcass (I th ), the model introduced a recovery factor (R f ) to consider this aspect with an uniform distribution ranging from 0.5 to 1.5 log 10 , using the information reported by O'Brien et al (2004). Bacon et al (2000) reported a reduction in the level of the microorganisms on the carcass compared to the hide level.…”
Section: Processingmentioning
confidence: 99%
“…Conventional IMS involves incubating 1 mL of enrichment with immunomagnetic beads before collecting the beads and plating, 8 which works well for small sample demand. When demand exceeds 10 samples, its use becomes prone to human errors and is tedious.…”
Section: Resultsmentioning
confidence: 99%
“…Factors which may influence prevalence include the sampling site choice (Reid et al, 2002;Kalchayanand et al, 2009), feeding systems and season (Rhoades et al, 2009). The concentration of E. coli O157 on the hides is typically around 100 CFU/cm 2 (Arthur et al, 2004;O'Brien et al, 2005).…”
Section: Slaughter and Processingmentioning
confidence: 99%